Penggambaran Peran Ayah dalam Film Sejuta Sayang Untuknya - Dino Saputra; Dyah Kusumawati (UNIVERSITAS KALBIS, 2022)
Film is a means of entertainment that has a high enough appeal in various circles of society. Film as a message medium has an entertaining nature that makes the audience unaware that the message from it penetrates the subconscious which can affect the mindset and attitude of the audience. The film Sejuta Sayang Untuknya is one of the family films that has successfully made the audience cry because the storyline is very touching, so it can be said that the film Sejuta Sayang Untuknya can be well received by the Indonesian people. Family is one of the smallest components of society. From a harmonious family it will produce a harmonious society as well. One of the reasons for the harmony of a family is the role of the father. This study aims to determine what the depiction of the father's role in the film Sejuta Sayang Untuknya. This study uses qualitative research methods with Charles Sanders Peirce's semiotic analysis method which analyzes a sign into the meaning of the sign, object, and interpretant. The results of this study indicate that the meaning of the sign, object, interpretant of Sagala is a father who is very responsible for his family and also that Sagala never gives up to make her child happy with the work she does even though Sagala's job does not stay somewhere.